Combining 3-dimensional degradable electrostatic spinning scaffold and dental follicle cells to build peri-implant periodontium - Ximu Zhang; Xiaoyan Zhou; Deyu Hu (Dental Hypotheses, 2013)
Introduction: Some inevitable problems, such as concentrated bite force and lacked ability of self-renewal, are proved to be the major challenge in the management of implants failures. Thus, it is meaningful to find an ideal dental implant harboring its own peri-implant periodontium, just as the natural teeth. Various studies attempted to reconstruct the periodontium around implants, but unfortunately, it was previously revealed that the artificial periodotium around implants was just a wilderness of fibers, while without the physiological function of natural periodontium, like sensory and homeostatic. The Hypothesis: In this paper, we propose a hypothesis that a modified three-dimensional scaffold with reconstructed peri-implant tissues can be a network for stem cells differentiation. After seeded on the scaffold, stem cells produce various growth factors and differentiate to different orientations in places necessary. This hypothesis, if proven to be valid, will offer a novel and effective therapy for the restoration of missing teeth by implant. Evaluation of the Hypothesis: The scaffold involves three different tissues. Though degradation rate of electrospinning scaffold is under control, its degradation rate should be in consistent with the generation of three tissues. Therefore, the relative experiments are necessary to define the best rate of degradation. Further verification is necessary to check whether the rebuilt cementum, bone and periodontium are strong enough to keep the implant stable and maintain its function.